mito de Tirésias revisitado: Ética & estética na ótica do cinema - Mucci, Latuf Isaias (Amaltea. Revista de Mitocrítica, 2010)
Taking a concept of “ethics” and “aesthetics”, and of their essential relationship concerning conflicts, harmony and conjugation, this essay revisites the greek myth Tiresias, semiotically translated by many languages of art, among which the cinema, from which is taked, as an emblem, the homonymous film by Bertrand Bonello.